Primary Orbital Myxoid Liposarcoma: A Case Report and Review of Literature - Niu, Chen; Rana, Netra; Min, Zhi Gang; Zhang, Ming (Asian Journal of Medical Sciences, 2013)
Liposarcomas are common malignant soft-tissue tumors, which come from primitive mesenchymal cells and differentiate into adipose tissue. These tumors are more commonly found in lower limbs and retroperitoneal region but also reported in pharynx, lung, liver, digestive tract, diaphragm, as well as in the spermatic cord. We reported a case of primary orbital myxoid liposarcoma in a 20-year-old female patient presented with a painless proptosis of the right eye. The mass was pathologically diagnosed as a myxoid liposarcoma. The tumor recurred in 9 months after surgical intervention. The second surgery was performed and followed by postoperative local radiotherapy. No recurrence has been reported after one year of follow-up. We highlighted the role of CT and MRI findings in the tumor diagnosis and the importance of local radiotherapy after surgery. Asian Journal of Medical Science, Volume-4 (2013), Pages 28-32 DOI: http://dx.doi.org/10.3126/ajms.v4i4.8311